School organizational climate and effectiveness of in-service training as predictors of teaching competence of primary school music teachers in the central zone of Peninsular Malaysia - Samsudin, Mohd Afiq Syimir; Abdullah, Arnida; Abdul Kadir, Suhaida (Human Resource Management Academic Research Society, 2023)
This study aims to identify the influence of school organizational climate factors and the effectiveness of in-service training on the teaching competence of primary school music teachers in the middle zone, of Peninsular Malaysia. In addition, the level of each variable and the relationship between the three variables were also studied. A quantitative approach that emphasizes correlational research design is used in this study where data is collected using a questionnaire. A total of 315 music teachers from the central zone of Peninsular Malaysia were involved based on multi-stage cluster sampling. The research instrument used to measure school organizational climate, the effectiveness of in-service training, and music teacher teaching competence is an adaptation of the Organizational Climate Description Questionnaire for Elementary School (OCDQ-RE) by Hoy et al (1991), Kirkpatrick's Assessment (1994) and Music Teachers Competence Assessment Sheets (MTCAS) by (Adeola, 2019). The data obtained was analyzed using descriptive statistics such as mean, standard deviation, and percentage as well as correlation and regression inference statistics to answer the research questions that had been formed. The results of the descriptive analysis of each variable show the school's organizational climate (M=2.835, SD=0.263), the effectiveness of in-service training (M=3.863, SD=0.608), and teaching competence (M=2.857, SD=0.603). Meanwhile, the results of the inference analysis show that school organizational climate and the effectiveness of in-service training have a moderately strong relationship (r=0.359, p<0.01 and r=0.490, p<0.01) and there is a significant positive influence (?=0.058) on teacher teaching competence music. This study is expected to help schools and the Malaysian Ministry of Education in improving efforts towards the preparation of primary school music teachers who are more competent in realizing national education goals and providing added value in education administration.